Analisis Knowledge Management dan Disiplin Kerja terhadap Kinerja Pegawai PT. Tri Tunggal Putra - Cut Fa Alhamahaa Magrit Damayanti Muli; Gendut Sukarno (Universitas Batanghari, 2023)
In this era of competition, knowledge is an important factor for a company, therefore knowledge management and work discipline are needed which are considered to be able to make a good participation as human resources, especially in the world of work. The purpose of this study is to determine the impact of knowledge management and work discipline on employee performance at PT. Tri Tunggal Putra. This study is a quantitative study that uses a questionnaire as a data collection method. The population included in this study is the security staff at PT. Tri Tunggal Putra with a total of 724 security. Samples in PT. Tri Tunggal Putra as many as 66 security using random sampling technique. The data used are primary and secondary data. The analysis technique used is Partial Least Square (PLS). The results in this study indicate that 1) knowledge management is able to contribute to employee performance at PT. Tri Tunggal Putra, 2) work discipline able to contribute to employee performance at PT. Tri Tunggal Putra.